RESPON PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L.) VARIETAS CIHERANG PADA PEMBERIAN KOMBINASI DOSIS PUPUK ANORGANIK DAN PUPUK KANDANG AYAM - Jannah, Asmanur; Rahayu, Yayu Sri; Sulanjari, Kuswarini (Majalah Ilmiah SOLUSI, 2012)
The objective of this experiment is to find out the best combination rate of chicken manure and inorganic fertilizer for rice growth and yield. The experiment was conducted at Desa Kutawargi, Kecamatan Rawamerta, Kabupaten Karawang, Jawa Barat during dry season from April 2012 to October 2012. The method used in this experiment was Randomized Block Design (RBD) with nine treatments and three replication. The tretaments were the combination of inorganic fertilizer rate (Urea-SP36-KCl) and chicken manure. The experiment indicated that the application of the combination of inorganic fertilizer (N, P, K) and chicken manure significatnly affected plant high at 42 days after planting (DAT) but not siginificantly affected yield componets and yield. The highest yield was 7,08 t/ha GKG on the H treatment (275 kg Urea/ha + 50 kg Sp-36/ha + 80 kg KCl/ha + 2000 kg /ha chicken manure). The highest N, P and K absorption on 56 DAT was found on the C teratment (200 kg Urea/ha + 50 kg Sp-36/ha + 50 kg KCl/ha + 2000 kg chicken manure) and the lowest was found on the E treatment (200 kg Urea/ha + 50 kg Sp-36/ha + 80 kg KCl/ha + 1000 kg/ha chicken manure) althought both of them are not significantly different. Keyword: inorganic fertilizer, chicken manure, agriculture ministrialdecree number 40/2007